PENGARUH PEMASARAN DIGITAL DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN DESAIN INTERIOR PT. SERATUS KURANG SATU INTERIOR DI KOTA BEKASI - Iwan Kurniawan Subagja; Robi Wandono (Jurnal Ekonomi dan Industri, 2024)
The analyze the influence of digital marketing and price on interior design purchasing decisions at PT. Seratus Kurang Satu Interior Kota Bekasi. This research is included in the category of causal associative research using a quantitative approach. The population in this research is interior design users. PT. Seratus Kurang Satu Interior Kota Bekasi. The sampling technique used purposive sampling technique. The analytical method uses simultaneous and partially linear regression analysis. The results showed that in simultaneous or partially ways the digital marketing and price have a positive and significant on interior design purchasing decisions at PT. Seratus Kurang Satu Interior Kota Bekasi.